PELATIHAN PEMBUATAN POC KOHE KAMBING DI DUSUN BOGING, DESA BODAG, KECAMATAN KARE, KABUPATEN MADIUN - Fadilla Eka Rohcahyani; Ratna Mustika Wardhani; Akbar Hardyansah; Ajun Wahyu Pamungkas; Nafilatul Azizah (JURNAL DAYA-MAS, 2026)
Boging Hamlett, Bodag Village, has a large number of goat farmers, resulting in livestock manure waste that has not been optimally utilized and has the potential to cause environmental pollution. Through the Community Service Program (KKN), training and assistance were provided in the production of liquid organic fertilizer (LOF) from goat manure as an effort to reduce pollution, promote environmentally friendly agriculture, decrease the use of chemical fertilizers, and provide economic benefits to the community. This community service activity was conducted in Boging Hamlet, Bodag Village, Kare District, Madiun Regency by the supervising lecturer and Students of the 2025 Community Service Program (KKN) from the Faculty of Agriculture, Universitas Merdeka Madiun on December 13, 2025. The program consisted of educational sessions followed by hands-on training in the production of goat manure-based liquid organic fertilizer. The activity involved local farmer groups and community members. The materials used included one sack of goat manure, 2 liters of molasses, 2 liters of EM4, and clean water. The equipment used consisted of a 10-liter container, a hose, a stirrer, a hot glue gun, and a soldering iron. The results showed that the program successfully improved the knowledge and skills of farmers and community members in independently producing liquid organic fertilizer from goat manure. In addition to being used for personal agricultural needs, the fertilizer also has the potential to be marketed, thereby generating additional income for the community. Therefore, the utilization of goat manure-based liquid organic fertilizer not only supports agricultural productivity and environmental sustainability but also provides economic value for local communities.